Linear cavity Brillouin fiber laser with improved characteristics - Shirazi, Mohammadreza Rezazadeh; Harun, Sulaiman Wadi; Biglary, Mozhgun; Ahmad, Harith (Optical Society of America, 2008)
A configuration for linear cavity Brillouin fiber laser (BFL) generation is demonstrated using a standard single-mode fiber, two optical circulators, a 3 dB coupler, and a 95/5 coupler to allow high efficiency. With a Brillouin pump (BP) power of 13 dBm, the laser peak power is 12.3 dB higher than a conventional linear cavity BFL at an upshifted wavelength of 0.086 nm from the BP wavelength. In addition, it is revealed that the BFL peak power can be higher than the transmitted BF peak power when the BF power exceeds the second Brillouin Stokes threshold power.